Upaya Sosialisasi Penerapan Wajib Tahu Baca Al Qur’an dalam Pernikahan bagi Calon Mempelai - Suneth, Ibnu Sulthan; Sukmana , Hendra; Alamsyah, M. Arrizky (Universitas Muhammadiyah Sidoarjo, 2013)
This study aimed to explore the reality of the truth, in all religious affairs office, which in the regulations there is no requirement of knowing how to read al-Qur’an by the Office of Religious Affairs, but with the complex problems in the community. This research is ekssplortif-developmental, because it aimed to know the motive of the appearance of symptoms as well as to identify and describe the development perspective of religious development. The data collected through interviews or in-depth interviews, the source of information is taken from the relevant parties in the implementation of marriage, both institutional and personal, and the informants in this study are taken from the relevant figures. Based on the results of this study showed that the public understanding of the villages in the district of Temple quite well in terms of reading Al-Qur'an. This is supported by the socialization presence for bride who is recommended by for religious Affairs and other related institutions.